2020
DOI: 10.1016/j.artd.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Impingement Resulting in Femoral Notching and Elevated Metal-Ion Levels After Dual-Mobility Total Hip Arthroplasty

Abstract: A 60-year-old woman underwent revision total hip arthroplasty with a modular dual-mobility articulation for recurrent dislocation. At 1-year follow-up, the patient reported no dislocations but had occasional clicking and discomfort with extreme motion. A Dunn radiograph identified notching of the femoral stem, attributed to impingement. Metal ions were elevated without adverse local-tissue reaction. After 4.5 years of observation, the notch size remained stable. She denied pain. Neither stem fracture nor prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…These studies have focused on the modular junction between the cobalt DM shall and the acetabular shell as the source of metal ions. Conversely, Matzko et al reported elevated metal ion levels in two patients with femoral notching associated with DM impingement, including one patient included in this report [21]. In our present study, this was the only one of the 10 cases of notching with ion levels drawn.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…These studies have focused on the modular junction between the cobalt DM shall and the acetabular shell as the source of metal ions. Conversely, Matzko et al reported elevated metal ion levels in two patients with femoral notching associated with DM impingement, including one patient included in this report [21]. In our present study, this was the only one of the 10 cases of notching with ion levels drawn.…”
Section: Discussioncontrasting
confidence: 44%
“…A second concern with femoral neck notching is the possibility of stem fracture. No such cases were discovered in this study and no reports of stem fracture due to notching were encountered in our literature review [17,21,36,43]. It should be noted that prosthetic femoral neck diameters are designed to resist fracture while optimizing head-neck ratio, so there is a legitimate concern that notched stems with focally reduced cross-sectional area may indeed be at fracture risk.…”
Section: Discussionmentioning
confidence: 74%
“…They concluded that notching resulted from impingement against the posterior prominence of the metal shell, and after modifying the shell to reduce its prominence, no further cases of notching occurred. Similarly, Matzko et al [22] described a case of femoral notching from impingement against a dual mobility acetabular bearing. They determined that increasing acetabular anteversion greater than 25-30 degrees may be a risk factor for femoral neck notching with dual mobility or other hard acetabular bearings.…”
Section: Discussionmentioning
confidence: 93%
“…Patients may present with a snapping sensation or pain with hip motion. 24 Intraoperatively, ensuring that the acetabular shell is not proud and avoiding excessive dissection around the tendon aids in reducing the risk of injury. 23 Having greater than 8 mm of acetabular shell uncovered anteriorly is a risk factor for need for revision surgery.…”
Section: Impingementmentioning
confidence: 99%